THE 2022 SWEDISH PARLIAMENTARY ELECTION: POSITIONING OF LEFT AND RIGHT PARTIES - Pavlovic, Jovica; Filipović, Aleksa (Politeia, 2024)
This paper examines the socio-political divisions within the Kingdom of Sweden, in order to provide an analytical insight into the positioning of Swedish parties during the campaign for the 2022 parliamentary elections (for the Riksdag). This analysis consequently contributes to the understanding of the election results achieved by major Swedish parties. Therefore, the first objective of the paper involves providing an analysis of party programmess and election results, while the second objective of the research aims to identify dependent and independent variables that contributed to the positioning and the subsequent success/failure of the eight largest Swedish parties in the parliamentary elections held in September 2022. By applying the method of discourse analysis and the method of document/data analysis, different strategies of party positioning are studied, with Lipset and Rokkan’s (1967) theory of party alignment being utilised as the theoretical framework; with a special emphasis on their theory of social cleavages. The paper begins with the hypothesis that pre-election campaigns of Swedish parties were mostly influenced by their need to position themselves in relation to two topics; the topic of immigration and the topic of health and educational system reform. The results of the research indicate that Swedish parties are increasingly more ready to change their historically recognisable attitudes and positions in line with current issues, in order to achieve positive election results. This trend is partially responsible for changes in the Swedish party system, which – however – remains partially intact for the time being, as can be seen from the outcome of the election.